KOMUNIKASI PEMASARAN DINAS PARIWISATA LAMONGAN DALAM MENGEMBANGKAN INDONESIA ISLAMIC ART MUSEUM SEBAGAI WISATA RELIGI - Abdul Ghofur (Universitas Muhammadiyah Jember, 2018)
This research is about Marketing Communication of religious tourism in Lamongan Regency, which is interesting to study, because Lamongan Regency is rich in various kinds of new tourism potential to be developed, one of which is the Indonesian Islamic Art Museum tour. However, the Department of Tourism and Culture has not been able to maximize the important role in the development of tourist attraction. So this research aims to know and describe marketing communication strategy and the obstacles faced by Tourism and Culture Department in developing Tourism in Lamongan regency, and also know how visitor response to tour Indonesian Islamic Art Museum.This research is done the location of Tourism and Culture of the Lamongan Regency. The problem of this research is how the marketing communication strategy and the obstacle of Tourism and Culture Department develop tourism Indonesian Islamic Art Museum in the Lamongan regency and how the visitor response to tour Indonesian Islamic Art Museum. This research uses a qualitative descriptive qualitative paradigm method through various stages of preliminary observation, interview, and documentation related to the marketing communication strategy of the Tourism and Culture Department.The results showed that the implementation of the marketing communication strategy of Tourism and Kebudayan Department in developing tourism Indonesian Islamic Art Museum by doing stages knowing the potential of tourism Indonesian Islamic Art Museum, planning, implementation, and evaluation. Then the obstacles found in the implementation of marketing communication strategy is the lack of funds, communicators, messages, and media. Then the response of visitors is satisfied with the facilities and infrastructure of tourist Indonesian Islamic Art Museum.Keywords: Marketing Communication, Tourism and Culture Department.